Dexamethasone potentiates the insulin-induced Srebp-1c expression in primary rat hepatocytes - Yan Zhang; Xiangming Fang; Fen Shuang; Guoxun Chen (Food Science and Human Wellness)
The impacts of dexamethasone (Dex) and thyroid hormone T3 on the insulin-stimulated Srebp-1c expression were studied in primary rat hepatocytes. Primary hepatocytes from Sprague-Dawley rats were isolated, cultured and treated with insulin in the presence or absence of the indicated reagents over time. The mRNA levels of indicated genes were determined using real-time PCR. Insulin treatment induced the Srebp-1c expression and suppressed the Pck1 expression in a time-dependent manner. Dex treatment alone reduced the Srebp-1c expression, whereas potentiated the insulin-induced its expression, which reached to a level that was higher than the insulin alone group. On the other hand, insulin treatment completely suppressed the Dex-induced Pck1 expression in the same cells. T3 treatment did not affect the expressions of Srebp-1c and Pck1 alone or in the presence of absence of insulin or Dex. Interestingly, insulin treatment induced the Rxrg mRNA expression level in the absence or presence of T0901317, a specific agonist for the liver X receptor. Dex and insulin mutually affect each other’s ability to regulate the expression levels of hepatic genes involved in glucose and fatty acid metabolism. Insulin induced Rxrg expression in primary hepatocytes, which may contribute to the induction of Srebp-1c expression in the same cells.